Features of the tasks of identifying and observing groups of unmanned letter vehicles - Kartashov V.М.; Pososhenko V.А.; Kapusta, A.I.; Rybnykov, M.V.; Pershin, E.V. (Radiotekhnika, 2022)
The current trend towards increasing the efficiency of UAV use is the transition from their single use to group use. In accordance with this, when building a complex integrated system for detecting and monitoring UAVs, including various information channels, it is advisable to take into account the features of the system functioning associated with the detection of groups of UAVs. The article discusses the information, energy and search capabilities of individual detection tools being a part of the integrated UAV surveillance system in order to build an effective algorithm for joint processing of incoming input signals, taking into account various capabilities of individual channels (in terms of range, recognition, etc.). An optimal algorithm for detecting groups of UAVs in a complex integrated system combining detection decisions made in private channels is synthesized. According to the synthesized algorithm, complex processing consists in summing up the solutions of individual detectors with some weights determined by the quality of the decisions made in the channels. The quality of solutions, in turn, depends on the technical means used in the channels and the conditions of observation. A sequence for solving a set of interrelated tasks in a complex integrated UAV surveillance system as the group target approaches the protected object is proposed. The sequence includes the following operations: identification of a group target (energy detection); estimation of coordinates of a group of objects; spatial resolution and determination of the number of vehicles in a group; recognition (type determination) of each individual device; assessment of the coordinates of each aircraft separately; determination of the composition of the group (homogeneous, heterogeneous); determination of the specialization of the group and revealing the nature of its tasks.